2010
DOI: 10.1537/ase.100302
|View full text |Cite
|
Sign up to set email alerts
|

Porotic hyperostosis and cribra orbitalia: the erythropoietic response to iron-deficiency anaemia

Abstract: A recent paper by Walker et al. (2009) states that iron-deficiency anaemia can no longer be regarded as being a cause of porotic hyperostosis (PH) or cribra orbitalia (CO). It is argued here that this conclusion is not supported by the current literature on iron-deficiency anaemia and associated haematopoietic responses or consequences to this condition. Indeed, iron-deficiency anaemia is still a plausible candidate in any differential diagnosis of lesions identified as PH and/or CO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
83
0
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(92 citation statements)
references
References 17 publications
(13 reference statements)
1
83
0
8
Order By: Relevance
“…Reduction in diet quality is often associated with the development of cranial lesions known as cribra orbitalia (CO) and porotic hyperostosis (PH) that represent an adaptive reaction of skeletal tissue to red bone marrow hyperplasia in response to childhood hemolytic or megaloblastic anemias (44). In regions where genetic hemoglobinopathies are rare, these lesions signal chronic anemia episodes during childhood caused by insufficient dietary iron, vitamin deficiencies, or loss of iron because of intestinal parasites (44,45). To analyze the relationships between stable isotope values and anemia indicators (CO and PH present = 1, absent = 0) (Dataset S2), we performed univariate logistic regressions with δ (Fig.…”
mentioning
confidence: 99%
“…Reduction in diet quality is often associated with the development of cranial lesions known as cribra orbitalia (CO) and porotic hyperostosis (PH) that represent an adaptive reaction of skeletal tissue to red bone marrow hyperplasia in response to childhood hemolytic or megaloblastic anemias (44). In regions where genetic hemoglobinopathies are rare, these lesions signal chronic anemia episodes during childhood caused by insufficient dietary iron, vitamin deficiencies, or loss of iron because of intestinal parasites (44,45). To analyze the relationships between stable isotope values and anemia indicators (CO and PH present = 1, absent = 0) (Dataset S2), we performed univariate logistic regressions with δ (Fig.…”
mentioning
confidence: 99%
“…A provocative paper by Walker et al (2009) somewhat reinvigorated such studies by challenging the well-established interpretation of cribra orbitalia and porotic hyperostosis as indicators of childhood iron deficiency. They posited that iron deficiency could not physiologically cause the lesions associated with marrow hyperplasia, although this assertion has been challenged by other researchers (Oxenham and Cavill 2010;Mays 2012). Further research has concluded that, while iron deficiency may not be responsible for the lesions, it is the end result and part of the body's defence mechanism against infection (Rothschild 2012;Steyn et al 2016).…”
Section: The Palaeopathology Of Childhoodmentioning
confidence: 99%
“…Their effect in past populations was undoubtedly enhanced by iron loss from diarrheal diseases in poor hygiene environments. However, Oxenham and Cavill (2010) claimed that iron-deficiency hypothesis was still a valid explanation of high frequencies of porotic hyperostosis and cribra orbitalia in skeletal samples.…”
Section: Cribra Orbitalia and Porotic Hyperostosismentioning
confidence: 99%